THE STRATEGY OF RESTRUCTURING TECHNOLOGICAL STRUCTURES OF THE DORNATURING PROCESS - Oqyo’lova Nigora Inobidin qizi (Bright Mind Publishing, 2025)
This article covers the process of treating dorns onto various hollow hole surfaces. This process improves surface cleanliness, the quality level will be higher. In the decoration of deep holes of small diameter, it is desirable to use methods that provide high animosity and surface purity, working ability of details, as well as their rigidity in a state not less than HRC≤445. These include dornamon, flashing methods.
Keywords: Dornovka , Drilling, Punches ,Zenkers , Sinks Lathe.